ABDIMAS SMP NEGERI 7 DENPASAR - Arjaya, Ida Bagus Ari; Susrawan, I Nyoman Adi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
SMP Negeri 7 Denpasar is one of the leading schools located in the City Center, namely Jalan Gunung Rinjani, Denpasar. This school has many achievements, both in the academic field and in the non-academic field. In the academic field, SMP Negeri 7 Denpasar is one of three school public schools that have passed verification from the Education Office to implement UNBK. SMP Negeri 7 Denpasar also received an award as one of the schools with integrity in the implementation of National Examination with a value of 9.5. Although most of the teachers at SMP Negeri 7 Denpasar have applied the student active learning approach, in reality teachers find it difficult to implement e-learning  models. Related to similar aspects, namely learning problems. From the aspect of library facilities, SMP Negeri 7 Denpasar already has a representative library and is very comfortable to be used by students both for learning and doing assignments .. But the obstacles or problems here are the types of reading books and subject books in SMP Negeri 7 Denpasar still classified less so students only get reading literature or limited learning resource books. The method used in this study is the interview method, namely in-depth interviews with informants, discussion methods, methods of active participation, demonstration methods, and methods of analyzing the understanding of trainees' teachers (pretest and post test) using a t-test. The results of the analysis show that there are significant differences (p = 0.001 <?) of the teachers' understanding in SMP Negeri 7 Denpasar between before and after participating in e-learning training.